Effects of Erythropoietin in Murine-Induced Pluripotent Cell-Derived Panneural Progenitor Cells - Nils Offen; Johannes Flemming; Hares Kamawal; Ruhel Ahmad; Wanja Wolber; Christian Geis; Holm Zaehres; Hans R. Schöler; Hannelore Ehrenreich; Albrecht M. Müller; Anna-Leena Sirén (BMC, 2013)
Abstract Induced cell fate changes by reprogramming of somatic cells offers an efficient strategy to generate autologous pluripotent stem (iPS) cells from any adult cell type. The potential of iPS cells to differentiate into various cell types is well established, however the efficiency to produce functional neurons from iPS cells remains modest. Here, we generated panneural progenitor cells (pNPCs) from mouse iPS cells and investigated the effect of the neurotrophic growth factor erythropoietin (EPO) on their survival, proliferation and neurodifferentiation. Under neural differentiation conditions, iPS-derived pNPCs gave rise to microtubule-associated protein-2 positive neuronlike cells (34% to 43%) and platelet-derived growth factor receptor positive oligodendrocytelike cells (21% to 25%) while less than 1% of the cells expressed the astrocytic marker glial fibrillary acidic protein. Neuronlike cells generated action potentials and developed active presynaptic terminals. The pNPCs expressed EPO receptor (EPOR) mRNA and displayed functional EPOR signaling. In proliferating cultures, EPO (0.1-3 U/mL) slightly improved pNPC survival but reduced cell proliferation and neurosphere formation in a concentration-dependent manner. In differentiating cultures EPO facilitated neurodifferentiation as assessed by the increased number of γ-III-tubulin positive neurons. Our results show that EPO inhibits iPS pNPC self-renewal and promotes neurogenesis.